1970
DOI: 10.1126/science.170.3965.1412
|View full text |Cite
|
Sign up to set email alerts
|

Fluorocitrate Inhibition of Aconitase: Relative Configuration of Inhibitory Isomer by X-ray Crystallography

Abstract: The fluorocitrate isomer that is a strong inhibitor and inactivator of aconitase has been shown by x-ray crystallographic studies on the rubidium ammonium salt to have the configurations (1R : 2R) or (1S : 2S) 1-fluoro-2-hydroxy-1,2,3-propanetricarboxylic acid. A possible mechanism for the action of fluorocitrate is proposed which involves the 1R : 2R isomer suggested from biochemical data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

1972
1972
2011
2011

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(28 citation statements)
references
References 12 publications
2
26
0
Order By: Relevance
“…Interestingly, many mutants in this class are involved in acetate metabolism, including TCA cycle genes, suggesting flux of bromoacetate through metabolism as a mechanism of detoxification. This is not without precedent as fluoroacetate enters the acetate metabolic pathway, and its toxicity is due to the lethal synthesis of the aconitase inhibitor, fluorocitrate (28). Also prevalent in this class are genes involved in synthesizing and reducing ubiquinone and genes in the cysteine biosynthetic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, many mutants in this class are involved in acetate metabolism, including TCA cycle genes, suggesting flux of bromoacetate through metabolism as a mechanism of detoxification. This is not without precedent as fluoroacetate enters the acetate metabolic pathway, and its toxicity is due to the lethal synthesis of the aconitase inhibitor, fluorocitrate (28). Also prevalent in this class are genes involved in synthesizing and reducing ubiquinone and genes in the cysteine biosynthetic pathway.…”
Section: Resultsmentioning
confidence: 99%
“…The synthesis and purification of the four different diastereoisomers of 2-fluorocitrate by Kun and Dummel (9) led to the identification of (Ϫ)-erythro-2-fluorocitrate, (2R,3R), as the inhibitory isomer of the enzyme (10). Kinetic studies of this compound with aconitase have yielded a range of K I values and have demonstrated that depending on which substrate was used in the studies, inhibition may be either competitive or noncompetitive and that this competition is reversible (11)(12)(13).…”
mentioning
confidence: 99%
“…By comparison with synthetic standards, the enzymic product was one of the erythro pair rather than the threo pair, in fact, the erythro isomer with (-) rotation (44). An X-ray structure of the mixture of epimeric kerythro 2-fluorocitrate salts established that (-) erythro had either 2R,3R, or 2S,3S absolute configuration (45). Here the matter rested, although Kun hypothesized correctly the 2R,3R structure based on anticipated regiospecificity of citrate synthase in putting an acetate (F-acetate) unit into the pro S arm of citrate (44).…”
Section: Fluorinated Substrate Analogsmentioning
confidence: 94%